Challenges and solutions for implementing knowledge management in knowledge-based companies supply chains - Torabi, Hassan; Maalmir, Ali; Ahmadi, Hossein (goodwood publishing, 2025)
Purpose: This study investigates challenges in implementing knowledge management systems within supply chains of knowledge-based companies in Iran and proposes actionable solutions for effective application. Methodology/Approach: A qualitative approach was employed, combining library studies, structured interviews with company founders, managers, and experts, and focus group discussions. A total of 182 propositions were categorized into six key themes—Financial Factors, Environmental Factors, Organizational Factors, Technology Factors, Personal Factors, and Strategic Action—and 31 subcategories. Results/Findings: The research identified significant obstacles, including inadequate planning, insufficient training, unclear organizational roles, regional influences, political challenges, lack of awareness regarding benefits, and poor financial management. Recommended solutions include creating detailed plans, appointing dedicated roles for knowledge management, improving training, fostering adaptability, and optimizing financial management practices. Conclusions: A systematic, proactive approach integrating strategic planning, cultural considerations, and flexible frameworks is essential for overcoming barriers. These measures enhance supply chain management and bolster competitiveness in a knowledge-driven economy. Limitations: This study is specific to knowledge-based companies in Iran and may not reflect industries or regions with differing contexts. Contribution: The findings provide valuable insights for policymakers, academics, and practitioners aiming to optimize knowledge management implementation, supporting innovation and efficiency in supply chains.